EFEKTIVITAS LEMBAGA ADAT DALAM PENGELOLAAN HUTAN ADAT RIMBO BULIM KABUPATEN BUNGO: The Effectiveness of Indigenous Institutions in Forest Management of Rimbo Bulim Indigenous, Bungo District - Rince Muryunika; Dodi Ir; Marwoto Marwoto (Fakultas Kehutanan Universitas Jambi, 2022)
ABSTRACT Rimbo Bulim customary forest management cannot be separated from the involvement of indigenous peoples who have roles as law enforcers and supervisors. This study aims to determine the effectiveness of customary institutions, whether they are running well and effectively and whether they have a positive or negative impact on the sustainability of customary forests. The results of the study stated that since the formation of the customary forest management group (KPHA) in 2013 until now, the existence of customary forests has improved, as evidenced by the absence of illegal logging and land clearing activities without permits, this can also be seen in the implementation of mutually agreed sanctions. The existence of traditional institutions is able to control the community around the forest. Keywords: Traditional institutions, forest management, local community, customary sanctions ABSTRAK Pengelolaan hutan adat Rimbo Bulim tidak terlepas dari keterlibatan masyarakat hukum adat yang memiliki peran sebagai penegak aturan dan pengawas. Penelitian ini bertujuan untuk mengetahui efektivitas lembaga adat apakah sudah berjalan dengan baik dan efektif dan apakah memberikan dampak positif atau negatif terhadap kelestarian hutan adat. Hasil penelitian menyebutkan bahwa semenjak dibentuknya kelompok pengelola hutan adat (KPHA) tahun 2013 hingga saat ini, keberadaan hutan adat sudah mengalami perbaikan terbukti sudah tidak adanya kegiatan perambahan dan pembukaan lahan tanpa izin, hal ini juga dapat dilihat berlakunya sanksi yang telah disepakati bersama. Keberadaan lmebaga adat mampu mengendalikan masyarakat sekita hutan. Kata Kunci: Lembaga adat, pegelolaan hutan, masyarakat lokal, sanksi adat